State and Local Perspective on Implementation of the Centers for Disease Control and Prevention Dog Confinement Agreement. (1st June 2015) - Zaganjor, I.; Sinclair, J. R.; Coleman, M. S.
Summary: The Centers for Disease Control and Prevention (CDC) works in conjunction with state, territorial, local and tribal agencies (STLTAs) to prevent the transmission of infectious agents. Issuance of confinement agreements using CDC Form 75.37 'Notice to Owners and Importers of Dogs' to importers of dogs that are not vaccinated or incompletely vaccinated against rabies is part of the agency's regulatory programme to prevent the entry of dogs infected with rabies. Although this is a regulatory programme that depends heavily on partnerships between CDC and STLTAs, CDC had never formally evaluated the acceptability of the confinement agreement process with these partners. Thus, a short survey of nine STLTAs was conducted to evaluate whether these partners have enough personnel and resources to implement the regulation and their general opinions of the confinement agreement process. The results illustrate that CDC partners are dissatisfied to some extent with the process, and there are multiple issues limiting their success in enforcing the regulation.